SPECTROSCOPIC VARIABILITY OF THE SUPERGIANTS HD21389 AND HD187982 - Maharramov, Y. M.; Baloglanov, A. Sh. (Одеські астрономічні публікації, 2016)
It has been revealed that absorption in the line of Hα has complex structure in the spectrum of the star HD21389 depending on the activity phase of the atmosphere. The profile of the line has inverse P Cyg type in the active phase of the star atmosphere. The emission components in the red and violet wing of the profile form and disappear. All the measured parameters of the Hα and Hβ lines change. It is supposed that such variations may be due to non-stationary and strong flow substance in the atmosphere of these stars. Appearance and disappearance of asymmetry in the profile of NaID doublet and formation of the Hα line type inverse P Cyg occurs synchronously in an active phase of the atmosphere of HD 21389. We assume that these changes are formed under the influence of the general mechanism which might be responsible for the observed variation is the growth of the envelope of the star with a following ejection of matter. Our researches showed that the values of radial velocity of the FeII lines change with time. However, we found no correlation of these changes with the period of 7.7 days found by earlier authors.